Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

It is a question from a quiz.

The following is the whole question.

Let \begin{eqnarray} \\f(x)=x^{3}-12x+\frac{48}{x}-\frac{64}{x^{3}} , \space x\in (-\infty ,0), \end{eqnarray} find $f^{-1}(x)$. Hint : $f(x)$ can be written in the form, like$(A+B)^{3}$.

The first thing I think is $(A+B)^{3}=A^3+3A^2B+3AB^2+B^3$, then try to make it become the the form of $A^3+3A^3B+3AB^3+B^3$. However, it it so difficult to obtain this form.

I need help.

Update : Now I have $\left(x - \frac 4x\right)^3$ but how to find the $f^{-1}(x)$ of $f(x)=\left(x - \frac 4x\right)^3$?


Thank you for your attention

share|improve this question

7 Answers 7

up vote 8 down vote accepted

Hint: Try matching first and last terms: $A^3 = x^3$ and $B^3=-\frac{64}{x^3}$ and check if it fits the other terms.

share|improve this answer
    
It should be $B^3=-\frac{64}{x^3}$, then $B=-\frac{4}{x}$. Thanks –  Casper Li Oct 16 '13 at 13:35
    
But how to find the $f^{-1}(x)$ of $\left(x - \frac 4x\right)^3$? –  Casper Li Oct 16 '13 at 13:40
    
You have $y=\left(g(x)\right)^3$, then $\sqrt[3]y=g(x)$ In this case multiply by $x$ at both sides and you get a quadratic: $x^2-\sqrt[3]yx-4=0$. –  Carlos Eugenio Thompson Pinzón Oct 16 '13 at 14:12

Hint: expand $$\left(x - \frac 4x\right)^3$$

share|improve this answer
    
But how to find the $f^{-1}(x)$ of $\left(x - \frac 4x\right)^3$? =( –  Casper Li Oct 16 '13 at 13:44
    
Try using the graph of the given function to graph its inverse. For example, see Wolfram Alpha –  amWhy Oct 16 '13 at 13:53
    
Short but so sweet :-)+ –  Babak S. Oct 23 '13 at 5:12

Hint: $y = \left(x - \dfrac4x\right)^3 \Longrightarrow x^2 - x\sqrt[3]{y} - 4 = 0$.

share|improve this answer

for $x \in (-\infty,0)$ the inverse function has the form

$$ f^{-1}(x)=\frac{1}{2}\left( \sqrt[3]{x}-\sqrt{\sqrt[3]{x^2}+16} \right) $$ As mentioned above we have

$y = \left(x - \dfrac4x\right)^3 \Longrightarrow x^2 - x\sqrt[3]{y} - 4 = 0$.

By solving the equation we get $$ x=\frac{1}{2}\left( \sqrt[3]{y}-\sqrt{\sqrt[3]{y^2}+16} \right), $$ and $$ x=\frac{1}{2}\left( \sqrt[3]{y}+\sqrt{\sqrt[3]{y^2}+16} \right). $$ The first expression is always negative (note $x \in (-\infty,0)$ but second is positive and not suitable for us. Thus, changing the variables, we get the inverse function.

share|improve this answer
    
How to obtain this ans? Thanks –  Casper Li Oct 16 '13 at 13:49
1  
see above........ –  Leox Oct 16 '13 at 13:55

$\left(x-\frac{4}{x}\right)^{3}$

share|improve this answer

First of all, $f$ does not have a inverse function because you always have two root of $f - y$. One positive root, one negative root.

If you add the constraints that $x$ is positive and $y$ is real, then there will be an inverse function. $$(x - \frac4x)^3=y$$

Since $y$ is real:

$$x - \frac4x=\sqrt[3]y$$

Since $x$ is not zero.

$$x^2 - 4=\sqrt[3]yx$$

Solve the quadratic equation:

$$x^2 - \sqrt[3]yx = 4 $$ $$(x-\frac{\sqrt[3]y}2)^2=4+(\frac{\sqrt[3]y}2)^2$$ $$ x - \frac{\sqrt[3]y}2 = \pm \sqrt{4+(\frac{\sqrt[3]y}2)^2}$$ $$ x = \frac{\sqrt[3]y}2 \pm \sqrt{4+(\frac{\sqrt[3]y}2)^2}$$

Since $x$ is positive, and the magnitude of the second term is greater than the first term, so you have to take the plus sign. This is your inverse function: $$f^{-1}(y) = \frac{\sqrt[3]y}2 + \sqrt{4+(\frac{\sqrt[3]y}2)^2}$$

If, however, you constrain $x$ to be negative, then take the minus sign above.

share|improve this answer

I first would eliminate the negative exponents of $x$ by multiplying $f(x)$ by $x^3$ to get $$g(x)=x^3f(x)=x^6-12\,x^4+48\,x^2-64$$ If you are right in assuming that $f(x)=h(x)^3$ then $g(x)=p(x)^3$ and $g'(x)=3p'(x)p(x)^2$ Now we assume that $p$ is a polynomial then $$p(x)^2 \mid \text{gcd}(g(x),g'(x))$$ and $$\frac{g(x)}{\text{gcd}(p(x),p'(x))} \mid p(x)$$

We get $$p'(x)=6\,x^5-48\,x^3+96\,x$$ and $$\text{gcd}(p(x),p'(x))=x^4-8\,x^2+16$$

$$\frac{g(x)}{\text{gcd}(p(x),p'(x))}=x^2-4=(x-2)(x+2)$$ Because the degree of the last polynomial is $2$ we must have $$p(x)=x^2-4$$ (ignoring constant factors) We can check that $$x^6-12\,x^4+48\,x^2-64=(x^2-4)^3=(x-2)^3(x+2)^3$$ and so $$f(x)=(x-\frac{4}{x})^3=(\sqrt{x}-\frac{2}{\sqrt{x}})^3 (\sqrt{x}+\frac{2}{\sqrt{x}})^3$$

Now let's solve $$(x-2/x)=y$$ for $x$. By multiplying the equation by $x<$ we finally get the quadratic equation $$x^2-yx-2=0$$ and get

$$x=-{{\sqrt{y^2+8}-y}\over{2}} $$ $$x=+{{\sqrt{y^2+8}+y}\over{2}}$$

So we have two inverse images for each value $y$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.